Emergency Response and Disaster Risk Management in Yobe State, Nigeria - Isah, Nuraddeen Ibrahim (World Bank, Washington, DC, 2022)
Following the conclusion of the North-East Nigeria Recovery and Stabilization Programme (NENRSP) in June 2018, the UK Government agreed to support the continuation and scaling up of World Bank (WB)-executed post-RPBA (Recovery and Peace Building Assessment) work through the second phase of Governance Partnership Facility (GPF)-funded activity. This second phase of activity is entitled ‘Enabling Sustained Recovery in the Northeast’ (ENSURE). ENSURE, which focuses on the states of Adamawa, Borno, and Yobe, and on Federal Government institutions mandated to oversee recovery in the northeast, is implemented in close coordination with a second WB-executed project (financed through a European Union Trust Fund) that seeks to promote recovery-related financial governance reforms (including coordination) in Borno State. The ENSURE program is to operationalize and support the Government of Nigeria’s (GoN) implementation of the Recovery Strategy and Framework, as defined by the North-East (NE) Nigeria RPBA and Buhari Plan; and to identify practical recommendations for ongoing and future GoN and development partner operations and collaboration, including the Multi-sector Crisis Response Project (MCRP).